Palestinian Evangelicals - a theologically engaged anthropological approach - Rose, L (Routledge, 2019)
Christian theologians have grappled for centuries with the fact that they are not Jews, yet embedded in Jewish history. Situated in the context of a Jewish-centric State that has been welcomed by a majority of evangelicals worldwide as fulfilment of biblical prophecy (and supported by their financial, spiritual, and political investment), Palestinian evangelicals are an anomaly. While they share an evangelical commitment, they have a complex and difficult relationship with the Israeli state. This paper argues that the population of Palestinian evangelicals is most productively explored through a combined interdisciplinary approach of Theology and Anthropology: it reveals the historical theologies that have shaped Palestinian evangelical engagement with the Israeli state and their global faith family. The article argues that theologically engaged Anthropology can aid in uncovering the power relationships within a transnational religious movement